(untitled) (Praxis Educativa, 2023)
Training first-year students in the Teacher Training Program and Bachelor’s Degree in Geography, through the resources of virtual classrooms, favors their academic literacy because it promotes significant learning in their educational trajectory. From this perspective, it is essential to focus attention on teaching strategies in digital scenarios and this fact questions us: how to be a teacher in a digital classroom? How to redesign virtual classrooms just not to be not a mere repository of documents and become a place of exchanges and debates? This work explores and redefines the use of the virtual campus in relation to the didactic dimension. Its relevance lies in offering a proposal for pedagogical intervention in digital scenarios, as a contribution, to rethink our teaching decisions and, therefore, consider other ways of teaching and learning before the new generations of students who are protagonists of a techno cultural context.